Antimicrobial activities and phylogenetic study of bacteria associated with Cyperus rotundus rhizosphere from Cemoro Sewu Plateau, Indonesia - AMBARWATI AMBARWATI; SUBAGUS WAHYUONO; SUKARTI MOELJOPAWIRO; LANGKAH SEMBIRING; TRIWIBOWO YUWONO (Society for Indonesian Biodiversity, 2019)
Abstract. Ambarwati A, Wahyuono S, Moeljopawiro S, Sembiring L, Yuwono T. 2019. Antimicrobial activities and phylogenetic study of bacteria associated with Cyperus rotundus rhizosphere from Cemoro Sewu Plateau, Indonesia. Biodiversitas 20: 2206-2212. A study has been conducted to investigate the activity of bacteria isolated from the rhizosphere of Purple Nut Sedge (Cyperus rotundus) from Cemoro Sewu Plateu, Indonesia as antimicrobial agent and the molecular relatedness between the isolates with other bacteria based on phylogenetic tree analysis. A total of six bacteria were obtained and tested for their capability to inhibit the growth of test organisms using agar block method and characterized molecularly using 16S rDNA sequence analysis. It was observed that the six isolates demonstrated the ability to inhibit at least one of four test microorganisms growth, with a diameter of inhibition zone ranging from 8-35 mm. The CRC32 isolate was the best isolate in inhibiting Staphylococcus aureus ATCC 25923 with a diameter inhibition zone of 26 mm (strong), while isolate CRA8 was the best anti-Candida (showing 35 mm of inhibition zone). The phylogenetic tree analysis resulted in two genera, four isolates belonging to Bacillus, while the other two isolates were known related to Paenibacillus genus. BLAST analysis on the CRC 32 isolate revealed that it is closely related with Paenibacillus peroriae strain 3763 with 99% sequence similarities and CRA8 isolates demonstrated the highest similarity with Paenibacillus sonchi strain X19-5 (97%). The results of this study demonstrated that the bacterial isolates from plant rhizosphere of Cemoro Sewu Plateau were the members of the Bacillus and Paenibacillus genera and demonstrated the potential as antimicrobial agent.